Evaluasi Prosedur Pelaksanaan Klaim Asuransi Public Liability Pada PT. Jasaraharja Persero Padang Sidempuan Tk II - Elida Asma Hari, Siti Nur; Syahriza, Rahmi (Universitas Labuhanbatu, 2021)
If a customer is slow to pay the premium to the company, the company may refuse to delay paying the claim to the customer, and may even terminate the contract or agreement that has been concluded with the insured. The purpose of this study is to determine how the procedure for the implementation of liability insurance claims at PT Jasaraharja Persero padang Sidempuan Tk ll so that companies with customers can cooperate in a good way.then it will be continued by evaluating the procedure for implementing the claims of PT Jasaraharja Persero padang Sidempuan Tk ll effective for PT Jasaraharja Persero padang Sidempuan Tk ll. This type of research uses the type of descriptive research, the implementation of research conducted at PT Asuransi Jasaraharja Persero padang Sidempuan Tk ll with data collection methods, namely observation and internship in the company.hence the conclusion that the procedure for implementing the claim carried out is less considered and effective. The application of actuarial science in the implementation of claims will help the company in recording so that it is easy to verify customer data that is still registered in the policyholder at PT Jasaraharja Persero padang Sidempuan Tk ll.